Modern anti-doping service progress trends: Win or loss? - Lubysheva, L. I.; Nazarenko, L. D. (Theory and Practice of Physical Culture, 2019)
Olympic sports may be defined as the specific activity of certain effects on the national policies and socio-economic situations. Competitive accomplishments in modern sports require high investments although they promote the nations, their images and improve the national positions for qualifications for the next Olympic Games. Analysis of the modern theoretical and practical literature on the doping issues in elite sports shows that many sport specialists, coaches and elite athletes believe that the modern Olympic movement is in serious crisis since the IOC, WADA and other international sports agencies pursue discriminatory policies disguised by the statutory anti-doping activity to marginalize national Olympic teams to simplify competitions for the US and other allies.